Strengthening Fraud Control Plan For Investigative Audit And Probity Audit In Fraud Detection - Abdullah, Muhammad Wahyuddin; Nurmelani; Andi Yustika Manrimawagau Bayan; Hadriana Hanafie (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2024)
The high number of corruption cases in local governments in Indonesia demands increased government attention to fraud cases. Opportunity for fraud can start from the planning stage to follow-up so that appropriate preventive and repressive handling efforts are needed. The Financial and Development Supervisory Agency has developed a fraud control plan and probity audit guidelines that are expected to be a solution to eradicate fraud in local governments. This study aims to analyse the effect of implementing investigative and probity audits on strengthening the fraud control plan in detecting fraud by auditors of the Financial and Development Supervision Agency of South Sulawesi and West Sulawesi. This study used quantitative with multiple linear analysis with Smart PLS 3.0 Software. Results found that investigative and probity audits positively affect fraud detection. Meanwhile, the fraud control plan does not strengthen the relationship between investigative and probity audits to fraud detection.